A critical review on mechanical micro-drilling of glass and carbon fibre reinforced polymer (GFRP and CFRP) composites. (1st April 2023) - Geier, Norbert; Patra, Karali; Anand, Ravi Shankar; Ashworth, Sam; Balázs, Barnabás Zoltán; Lukács, Tamás; Magyar, Gergely; Tamás-Bényei, Péter; Xu, Jinyang; Davim, J Paulo
Abstract: Recent trends in miniaturisation and high-strength fibrous composites encourage the use of mechanical micro-drilling technology of fibre-reinforced polymer composites (FRPs). Although severe expertise has been gained through the past few decades on the machinability of FRPs, this information cannot be directly adapted to the micro-drilling mainly due to the size effect. Therefore, the main aim of the present study is to comprehensively review challenges, recent experience, and future aspects of mechanical micro-drilling of glass and carbon fibre reinforced polymer (GFRP, CFRP) composites. The chip removal mechanisms of micro-drilling of FRPs are reviewed and compared to conventional-sized technologies. Furthermore, the micro-drilling-induced geometrical defects (delamination, burrs, fibre pull-outs etc. ) and the cutting energetics are also discussed. Moreover, the future aspects and research directions are highlighted in this growing research area. Graphical abstract: Image 1 Highlights: Challenges of micro-drilling of fibrous composites were discussed and compared to macro-drilling. Mechanisms of micro-drilling of FRPs are handled in an analogy of conventional drilling of FRPs considering CER. The lack of information on the micro-drilling of FRPs is highlighted. Future research directions and trends are discussed.